1970
DOI: 10.1111/j.1476-5381.1970.tb09903.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, metabolism and release of [3H]‐adrenaline by human platelets

Abstract: Summary1. Measurements were made of the uptake, metabolism and release of [3H]-adrenaline by human platelets in citrated plasma or in an artificial medium. 2. Radioactive adrenaline was not taken up at 0-2°C. At 370 C there was a slow uptake which continued for at least 5 hours.3. About half of the radioactivity in the platelets was intact adrenaline. The other half was an acidic metabolite from which adrenaline was released by acid hydrolysis. 4. The immediate uptake of adrenaline was proportional to its conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2
2

Year Published

1972
1972
1981
1981

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 17 publications
3
26
2
2
Order By: Relevance
“…For instance, it was found that labelled CA injected into rabbits, were highly concentrated in a platelet fraction rich in 5-HT organelles (Da Prada & Pletscher, 1969b). In addition it has been shown that isolated platelets take up CA in vitro (Born et al, 1958;Weissbach et al, 1958;Weil-Malherbe & Bone, 1958;Born & Smith, 1970;Boullin & O'Brien, 1970) and that 5-HT organelles isolated from rabbit platelets are also able to concentrate labeled CA in vitro (Da Prada & Pletscher, 1969a). Born & Smith (1970) have demonstrated that reserpine, which reduces 5-HT uptake by acting at the level of the 5-HT granular membrane (Pletscher, Burkard & Tranzer, 1967;Da Prada & Pletscher, 1969b), also impairs Ad uptake in intact platelets.…”
Section: Catecholamines and 5-hydroxytryptamine In Spd Rat Plateletsmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, it was found that labelled CA injected into rabbits, were highly concentrated in a platelet fraction rich in 5-HT organelles (Da Prada & Pletscher, 1969b). In addition it has been shown that isolated platelets take up CA in vitro (Born et al, 1958;Weissbach et al, 1958;Weil-Malherbe & Bone, 1958;Born & Smith, 1970;Boullin & O'Brien, 1970) and that 5-HT organelles isolated from rabbit platelets are also able to concentrate labeled CA in vitro (Da Prada & Pletscher, 1969a). Born & Smith (1970) have demonstrated that reserpine, which reduces 5-HT uptake by acting at the level of the 5-HT granular membrane (Pletscher, Burkard & Tranzer, 1967;Da Prada & Pletscher, 1969b), also impairs Ad uptake in intact platelets.…”
Section: Catecholamines and 5-hydroxytryptamine In Spd Rat Plateletsmentioning
confidence: 99%
“…Moreover, thrombin, which is known to release platelet 5-HT, ATP and calcium (typical constituents stored in the 5-HT organelles) was also able to release labelled Ad from platelets preloaded in vitro with this tritiated amine (Born & Smith, 1970). The present data obtained by measuring radioenzymatically the concentration of endogenous Ad, NA, dopamine and 5-HT in the subcellular structures isolated by subjecting rabbit platelet homogenates to density gradient centrifugation, directly demonstrate that 5-HT organelles are also the storage sites of the platelet CA.…”
Section: Catecholamines and 5-hydroxytryptamine In Spd Rat Plateletsmentioning
confidence: 99%
See 2 more Smart Citations
“…Imipramine was much less inhibitory than methysergide and the inhibition was not competitive. Human platelets take up 5-HT by a mechanism which causes it to be highly concentrated in intracellular storage granules and which is highly specific for 5-HT as far as the naturally occurring amines are concerned (for reviews, see Pletscher, 1968;Born, 1969); adrenaline is also taken up but much more slowly and concentrated far less (Born & Smith, 1970). It was of particular interest, therefore, to see which of our structural analogues of 5-HT could be taken up by platelets by a process similar to that for 5-HT.…”
Section: Inhibition Of Aggregationmentioning
confidence: 99%